Multivariational Inequalities and Operator Inclusions in Banach Spaces with Mappings of the Class $(S)_{+}$ - Mel'nik, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We prove theorems on the existence of solutions of variational inequalities and operator inclusions in Banach spaces with multivalued mappings of the class (S)+. We justify the method of penalty operators for variational inequalities.